DEFORESTATION IN THE DEMOCRATIC REPUBLIC OF CONGO AND CLIMATE CHANGE: AN ETHICAL ANALYSIS IN LIGHT OF LAUDATO SÍ - Lushombo, Léocadie (Asian Horizons, 2020)
Deforestation in the Democratic Republic of Congo (DRC) is not only a Congolese and central African issue, but is also a global problem. This paper argues that the destruction of tropical forests influences the planetary climate and presents the ways deforestation directly affects climate change in the world. It describes the historical, social, political, economic, and ecological causes of deforestation in the DRC and assesses the relevant power dynamics in the deforestation process. The paper then analyzes critical ethical issues of deforestation in light of Laudato Sí’s insights and the principles of environmental ethics. Finally, this paper argues that any preferential option taken for the poor should not leave them behind; rather it must include them in the dialogue and implementation of new strategies to combat deforestation and climate change. The practice of community forestry is a valuable response to Pope Francis’ call for an overall approach to deal with climate change. Ethical analysis in this paper uses the “Three-Stage Method” of James B. Martin-Schramm and Robert L. Stivers of “Cases Studies and Moral Deliberation.”